Endobronchial hamartoma; are the lines fading from the zebra? Case series and review of literature - Akesh Thomas; Jessee Woodall; Ghassan J. Wadhi; Paul R. Branca (Lung India)
Hamartoma is a common benign tumour of the lung. Although most pulmonary hamartomas are located within the lung parenchyma, rarely they present as endobronchial tumours. We are describing one case of a 75-year-old gentleman with endobronchial hamartoma removed via traditional flexible bronchoscopy and another case of a 55-year-old gentleman whose endobronchial hamartoma was diagnosed via robotic navigational bronchoscopy. We are also describing the salient features of three other cases of endobronchial hamartoma diagnosed at our institution in the last 13 years. With the emergence of advanced navigational bronchoscopy techniques, we predict that the incidence of identifying endobronchial hamartomas will increase.